Mining intelligence and knowledge exploration : third International Conference, MIKE 2015, Hyderabad, India, December 9-11, 2015. Proceeedings /: third International Conference, MIKE 2015, Hyderabad, India, December 9-11, 2015. Proceeedings. (2015) - Unknown
No abstract available